Application of lasers for corrosion cleaning of ancient textiles with metallic threads - Slavica Ristić; Slobodan Dragutinović; Joakim Striber (Zaštita Materijala)
Classical methods of corrosion cleaning of ancient textiles with metallic threads often do not produce the expected results. The use of lasers in the protection and conservation of cultural heritage items in recent years has an important role. The most complicated is the use of lasers in cleaning items that have a multicomponent structure, such as, combination of metal and fabric. This paper discusses the problem that appeared in the holdings of textiles Ethnographic Museum in Belgrade. We presents the results of the effects of Nd:Yag laser cleaning of ethnographic textile experimental samples with metallic threads. Cleaning effects was investigated by an optical and scanning electronic microscopy (OM and SEM) and EDX analysis. Parameters for successful and safe cleaning of corrosion products on the metal threads were determined for some exponats.